The Effect of Lego Play Activity Therapy on Anxiety Levels of Preschool Children (3-6 years) due to Hospitalisation - Sri Mujiyanti Mungalim; Ris Ris Rismawati (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
Preschoolers are early childhood where the child has not stepped on the school year unfolds aged 3-6 years. Like adults, children can also be stricken with an illness and require hospitalization for the diagnosis and treatment of disease.So that these conditions become a factor stressors in children can cause anxiety. Overcoming anxiety levels in children, nurses in providing interventions should consider the needs of children in accordance growth.One of the activities to reduce children's anxiety is playing lego. The purpose of this study was to determine the effect of therapeutic activity against anxiety level playing lego preschool children (3-6 years) due to hospitalization. The research design used in this study is a quasi-experimental design studies with a one-shot approach of case study.Respondents in this research were 22 children, where data collectionby distributing questionnaires anxiety levels to be completed by the parent / guardian respondents. Data retrieval performed twice, ie before therapy and after playing lego play therapy. Processing data using a computer program. The average level of anxiety before is 111.86 and after63.50, the results of analysis using parametric statistical tests Paired t-test results P value = 0.000 meaning <α (0.05) it can be concluded that there is a significant effect between the level of anxiety before and after play therapy. Recommended to apply play therapy to reduce anxiety levels of preschool children who are being Hospital treated nursery in Banten Hospital.Keywords: Therapeutic Activities; Lego;Anxiety; Hospitalization